Dampak Program Dana Desa Terhadap Pembangunan Pertanian Di Desa Seungai Arang Kecamatan Bungo Dani Kabupaten Bungo - Febrian, Rhonal; HD, Ernawati (JALOW | Journal of Agribusiness and Local Wisdom, 2022)
Village Funds are funds sourced from the State Revenue and Expenditure Budget (APBN) and are the obligation of the Central Government to allocate a transfer budget to the Village in the State Revenue and Expenditure Budget as a form of state recognition and appreciation to the Village, village funds are intended for the Village to finance government administration. , development, as well as community empowerment, and society. The existence of the Village Law and other regulations, has an impact on the size of the budget for village development, nationally the central government provides funds to villages for 2015 amounting to Rp.20,766,200,000, while in 2016 it is Rp. 46,982,080,000, in 2017 it is Rp. 60,000,000,000, in 2018 it is Rp. Rp.60,000,000,000 and in 2019 Rp.70,000,000,000 with the number of villages in Indonesia as many as 74,093. In addition to other sources of funds, the Village Fund Program obtained by villages throughout Bungo Regency in 2015 Bungo Regency received village funds of Rp. 38,514,584,000, In 2016 Bungo Regency received Village Funds of Rp. 86,289,072,644, In 2017 Bungo Regency received Village Funds of Rp. .109,907,883,000, in 2018 Bungo Regency received village funds of Rp. 99,662,383,000, and in 2019 Bungo Regency received village funds of Rp.114,776,496,000. Of the 17 sub-districts and 141 villages in Bungo district, Sungai Arang village, Bungo Dani sub-district, the impact of the Village Fund Program on Agricultural Development, because Sungai Arang Village has good agricultural land and potential and has many farmer groups, the success of agricultural development in the village From the village fund program, assistance from the district government is needed through the agricultural service agency or agricultural extension, related agencies in depth and sustainably, so that the village government and all farming communities can work together to manage and utilize village funds for farmer groups.